COVID-19 Pandemic & Bureaucracy: The Crisis Inside the Crisis - Roßmann, Katalyn; Wegner, Heike; Stark, Hans; Großmann, Gerd; Jansen, Andreas; Frangoulidis, Dimitrios (Frontiers in Public Health, 2021)
The Medical Intelligence & Information (MI2) Unit of the German Armed Forces (Bundeswehr) is experienced in crisis support in military missions since several years. It gained additional experiences during the current COVID-19 pandemic on different levels of the response to crisis and was requested to share findings and expertise with overloaded civil public health agencies inside Germany. Since the beginning of the pandemic, the unit is constantly developing new products for crisis communication, knowledge sharing techniques in new databases, dashboards for leadership and training for laypersons in contact tracing. Hence, trying to innovate in crisis since the first SARS-CoV-2-disease wave. During the second wave, the unit was requested to evaluate the outbreak management of different national civil public health agencies in southern Germany, and to support the development of dashboards in a comprehensive public health approach as a necessary start in towards digitalization.